Visual Basic® Style Guide, The - Patrick, Tim (Prentice Hall PTR Microsoft technologies series., 2000)
The essential companion for Visual Basic development teams and individuals. Master effective practices to create crystal-clear, reusable code Foster effective collaboration by maintaining reliable standards Acquire the mindset of a professional developer Use the comprehensive reference section to make your programs consistent and portable Works with all flavors of Visual Basic Professional best practices for programmers Guidelines for standard structure and syntax Foundational attitudes of quality development Complete reference section for all flavors of Visual Basic The essential companion for Visual Basic development teams and individuals. All effective teamwork is based on clear communication. In the field of software development, this means using consistent, documented conventions that can be easily understood and built upon by teammates, now and in the future. To meet this need, this handbook for Visual Basic programmers contains a comprehensive reference section covering nomenclature, instantiation, keywords, controls, user interfaces-every major VB concept, in all flavors of VB. And more than that, it promotes an attitude, an environment of the mind in which healthy Visual Basic programs are formed. The winning philosophy of The Visual Basic Style Guide will help your team develop its programming power through discipline, documentation, and professionalism. Build your development skills through: Application of proven and consistent style and user interface methodologies, Grounding in the foundational attitudes of discipline, planning, and ethics, and Getting to know the comprehensive, quick-access reference section. Even programmers working on individual projects will benefit from the enhanced professionalism that comes from consistency. Whether you're a experienced programmer, a team leader, or a manager, you'll appreciate the thorough coverage and the rigorous standards provided in The Visual Basic Style Guide .